The historical, theological and spiritual commonality between the monotheistic religions: a comparative approach between the Biblical Abraham and the Quranic Ibrahim - Tijani Boulaouali (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article deals with the Prophet Abraham as a historical, theological and spiritual commonality between the monotheistic religions: Judaism, Christianity and Islam. Although many centuries have passed from the historical context in which Abraham lived according to both the Quranic and biblical narratives, Abraham is still considered a factor of rapprochement among all followers of monotheism, whether Jews, Christians, and Muslims, in times of prosperity and crises, and moments of peace and wars as well. This article is divided into three chapters. Firstly, the fundamental term “Abraham/Ibrahim” is examined etymologically and semantically. Secondly, the figure of Abraham is discussed theologically both in the biblical and Quranic narratives. Finally, the shared aspects of Abraham between the three monotheistic traditions are analyzed, focusing on its historical, theological, and spiritual commonalities. In this article, we have adopted a comparative approach between the biblical Abraham and the Quranic Ibrahim, based on several biblical texts, especially in the Old Testament and Quranic verses. Finally, the main conclusion of this work is that Abraham, as a historical figure from whom all monotheists descend, is no longer related to the past only. He extends throughout history to the present and then to the future, as a symbol of religious, spiritual, and moral unity.